The Analysis of Society Preferences in Using MALFARMS Metaverse Application to Support Green and Sustainable Agriculture - Prasetyaningrum, Dian Islami; Maulidan, Mohamad; Yuswita, Effy; Kristiansen, Paul (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2025)
MALFARMS application itself is one example of technology implementation in the context of modern agriculture. MALFARMS is an agricultural optimization innovation through the metaverse concept based on Android Integrated Augmented Reality Technology. The optimization of farming activities through the provision of e-commerce plays a vital role in agricultural marketing. MALFARMS can also help optimize the agricultural process to minimize adverse environmental impacts. This study aims to analyze people's preferences for the MALFARMS application, describe what features support the MALFARMS application, and explore the MALFARMS application to achieve green marketing. The research method uses a quantitative approach with data analysis used in this study using Discrete Choice Experiment (DCE) Analysis. The DCE method was chosen because it considers other alternatives in the choice set in the MALFARMS feature. The research was conducted in Malang City, Malang Regency, and Batu City. Public preference for the MALFARMS application based on the results of conditional logit analysis shows that the MALFARMS application on product advertisements on the application display and innovative application display has a more excellent utility value than the application display with attractive application design, which is 0.892 and 0.701 respectively. The results of the conditional logit analysis of products labeled as non-organic and without claims have a more excellent utility value than organic products, which are 0.570 and 0.120, respectively. The results of the conditional logit analysis on E-Money and COD have a more excellent utility value than bank transfers, which are 0.492 and 0.504, respectively.